Carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite as well as preparation method and application thereof

By forming a lithium aluminate coating layer on the surface of lithium-rich lithium ferrite and then coating it with a carbon layer, the problem of poor air tolerance and conductivity is solved, achieving more efficient lithium ion release and increasing charging capacity.

CN119361866APending Publication Date: 2025-01-24GANFENG LITHIUM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411691668.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Lithium-rich lithium ferrate has poor air tolerance and conductivity in lithium-ion batteries, which makes it difficult for it to fully release lithium ions during the charge and discharge cycle, reducing the circulation capacity retention rate of the lithium-ion battery.

Method used

Use carbon-aluminum dual-layer covering technology, by forming lithium aluminum coating layer on the surface of lithium-rich lithium iron iron, and covering a layer of carbon layer on it to form a double-layer covering structure to improve its Air tolerance and conductivity.

Benefits of technology

Through the double -layer covering technology, the air tolerance and conductivity of lithium -rich lithium iron -rich are significantly improved, and its lithium nourishing performance in lithium ion batteries can more fully release lithium ions and increase charging capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361866A_ABST
    Figure CN119361866A_ABST
Patent Text Reader

Abstract

The invention provides carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite, which is characterized in that an aluminum source is used for reacting on the surface of lithium-rich lithium ferrite to coat a layer of lithium aluminate, and then a carbon source is used for coating to form the carbon-lithium aluminate double-coating layer coated lithium-rich lithium ferrite. The carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite disclosed by the invention has relatively good lithium supplement performance, and can be used as a lithium supplement agent for a positive electrode of a lithium ion battery, so that the service life of the lithium ion battery is prolonged, and the long cycle performance of the lithium ion battery is improved. In addition, the invention also provides a preparation method and application of the carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate, and a preparation method and application thereof. Background Art

[0002] During the charge and discharge cycle of lithium-ion batteries, the formation of the SEI film plays a vital role. It is a passivation layer formed by the reduction reaction of the electrolyte on the electrode surface, which can improve the performance and cycle life of lithium-ion batteries. However, the formation of the SEI film will also consume the active lithium ions in the positive electrode material, reducing the number of lithium ions that can be intercalated and deintercalated, and reducing the capacity retention rate of lithium-ion battery cycles. Therefore, lithium supplementation technology came into being.

[0003] The positive electrode lithium replenishment technology is simple to operate, safe and controllable. There is no need to increase or change the battery preparation process. It only needs to add a certain proportion of lithium replenisher during the positive electrode homogenization process to improve the performance of the prepared lithium-ion battery. In the field of positive electrode lithium replenishers, lithium-rich lithium iron oxide (Li5FeO4) materials have extremely high lithium replenishment capacity and have good compatibility with existing lithium iron phosphate and ternary positive electrode materials, which can effectively improve their long-cycle performance. However, lithium-rich lithium iron oxide has poor structural stability and is easily decomposed in humid air, thereby reducing the replenishment of lithium ions. Moreover, the FeO4 tetrahedrons in Li5FeO4 are structurally disconnected from each other, and the conductivity of lithium-rich ferrite is very low, close to zero. Therefore, unmodified lithium-rich ferrite is difficult to play its due role in the lithium replenishment application of lithium-ion batteries. In order to solve the problems of air tolerance and lithium replenishment performance of lithium-rich ferrite, the current mainstream coating method is to coat the surface of lithium-rich ferrite with a carbon layer to increase its air tolerance and conductivity. However, the traditional carbon coating method for coating lithium-rich ferrite is difficult to fully play the actual lithium replenishment effect of lithium-rich ferrite, and the air tolerance is poor. In summary, the use of lithium-rich ferrite as a lithium replenisher requires a new modification technology to increase the air tolerance of lithium-rich ferrite and improve its conductivity to increase the lithium ion content released by lithium-rich ferrite during the formation stage of lithium-ion batteries. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite and its preparation method and application, which can solve the technical problems that ordinary lithium-rich lithium ferrite has poor air tolerance and conductivity, and the charging capacity is difficult to fully release.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a carbon-lithium aluminate double-layer coated lithium-rich ferrite, wherein an aluminum source is used to react and coat a layer of lithium aluminate on the surface of the lithium-rich ferrite, and then a carbon source is used for coating to form a carbon-lithium aluminate double-layer coated lithium-rich ferrite.

[0006] Furthermore, the mass fraction of aluminum element is 0.2~5%, and the mass fraction of carbon element is 0.2~10%.

[0007] In a second aspect, the present invention provides a method for preparing a carbon-lithium aluminate double-layer coated lithium iron-rich lithium as described in any one of the above items, comprising the following steps: 1) Add a certain molar ratio of lithium source and aluminum source to lithium-rich lithium ferrite powder and mix them evenly; 2) heating and calcining the mixture obtained in step 1) under an inert atmosphere, and crushing it after cooling to obtain a lithium aluminate-coated lithium ferrite-rich lithium material; 3) The lithium aluminate-coated lithium ferrite-rich material obtained in step 2) is mixed with a carbon-containing compound, heated and calcined under the protection of an inert atmosphere, and crushed after cooling to obtain a carbon-lithium aluminate double-layer-coated lithium ferrite-rich lithium material.

[0008] Furthermore, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium oxide, and lithium peroxide, the aluminum source is at least one of aluminum oxide, aluminum hydroxide, and aluminum nitrate, and the molar ratio of lithium element to aluminum element is 0-1.5.

[0009] Furthermore, the coating temperature of lithium aluminate coating lithium-rich lithium ferrite is 600~900℃, and the coating time is 2~16h.

[0010] Furthermore, the coating temperature of the carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite is 400~700°C, and the coating time is 1~8h.

[0011] In a third aspect, the present invention provides a lithium-ion battery, comprising a lithium-ion battery comprising a lithium-ion battery comprising a carbon-lithium-aluminate double-layer coated lithium-rich lithium ferrate or a carbon-lithium-aluminate double-layer coated lithium-rich lithium ferrate obtained by the preparation method described in any of the above items.

[0012] The carbon-lithium aluminate double-layer coated lithium-rich ferrite and preparation method thereof of the present invention, the lithium-rich ferrite is uniformly mixed with an aluminum source and a lithium source, and reacts with the aluminum source, the lithium source and the surplus lithium in the lithium-rich ferrite at a high temperature to form a lithium aluminate coating layer on the surface of the lithium-rich ferrite, and then forms a carbon-lithium aluminate double coating layer by a carbon coating method. Compared with the ordinary carbon coating method, the lithium aluminate coating layer of the lithium-rich ferrite obtained by the present invention is formed by a chemical reaction with the lithium-rich ferrite at a high temperature, is tightly bonded to the surface of the lithium-rich ferrite and is not easy to fall off, and the carbon layer is coated on the surface of the lithium aluminate coating layer to increase the conductivity of the material, which can better resist moisture and carbon dioxide in the air, reduce the decomposition rate of the lithium-rich ferrite, and fully release lithium ions through good conductivity during the lithium replenishment process to achieve a good lithium replenishment effect.

[0013] The carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate and the preparation method thereof of the present invention form a lithium aluminate coating layer on the surface of the lithium-rich lithium ferrate particles after high-temperature calcination, and then the lithium aluminate-coated lithium-rich lithium ferrate is evenly mixed with a carbon-containing compound, and a carbon-lithium aluminate double coating layer is formed after high-temperature calcination. The obtained carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate can better resist moisture and carbon dioxide in the air, and can fully release lithium ions during the first charging process of the lithium ion battery, thereby increasing the charging capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a scanning electron microscope image of the material of Example 1; Figure 2 The XRD patterns of the materials of Example 1 and Comparative Example 1 after being placed in air with a dew point of -20°C for 1 hour; Figure 3 The charging performance diagram of the lithium batteries of Example 4 and Example 5 at a rate of 0.066C; Figure 4 This is a charging performance diagram of the lithium battery of Comparative Example 1 at a rate of 0.066C. DETAILED DESCRIPTION

[0015] See also Figure 1-Figure 4 In the first aspect, the present invention provides a carbon-lithium aluminate double-layer coated lithium-rich ferrite, wherein an aluminum source is used to react and coat a layer of lithium aluminate on the surface of the lithium-rich ferrite, and then a carbon source is used for coating to form a carbon-lithium aluminate double-layer coated lithium-rich ferrite.

[0016] Furthermore, the mass fraction of aluminum element is 0.2~5%, and the mass fraction of carbon element is 0.2~10%.

[0017] In a second aspect, the present invention provides a method for preparing a carbon-lithium aluminate double-layer coated lithium iron-rich lithium as described in any one of the above items, comprising the following steps: 1) Add a certain molar ratio of lithium source and aluminum source to lithium-rich lithium ferrite powder and mix them evenly; 2) heating and calcining the mixture obtained in step 1) under an inert atmosphere, and crushing it after cooling to obtain a lithium aluminate-coated lithium ferrite-rich lithium material; 3) The lithium aluminate-coated lithium ferrite-rich material obtained in step 2) is mixed with a carbon-containing compound, heated and calcined under the protection of an inert atmosphere, and crushed after cooling to obtain a carbon-lithium aluminate double-layer-coated lithium ferrite-rich lithium material.

[0018] Furthermore, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium oxide, and lithium peroxide, the aluminum source is at least one of aluminum oxide, aluminum hydroxide, and aluminum nitrate, and the molar ratio of lithium element to aluminum element is 0-1.5.

[0019] Furthermore, the coating temperature of lithium aluminate coating lithium-rich lithium ferrite is 600~900℃, and the coating time is 2~16h.

[0020] Furthermore, the coating temperature of the carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite is 400~700°C, and the coating time is 1~8h.

[0021] In a third aspect, the present invention provides a material, comprising the lithium ferrite-rich lithium ferrite coated with a double layer of carbon-lithium aluminate as described in any one of the above items, or the lithium ferrite-rich lithium ferrite coated with a double layer of carbon-lithium aluminate obtained by the preparation method described in any one of the above items.

[0022] It can be understood that there is no limitation on the type of the material. The material can be a lithium-ion battery or other materials, as long as it includes a carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate as described in any of the above items or a carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate prepared by the preparation method described in any of the above items. Example

[0023] Take 50g of lithium-rich lithium iron oxide material, add 1g of nano-aluminum oxide and 0.45g of lithium peroxide, mix well, and calcine at 600℃ for 10h; after cooling, take out and grind, add 5g of glucose, mix well, and calcine at 450℃ for 5h; after cooling, take out and crush, the target product is a carbon-lithium aluminate double-layer coated lithium-rich lithium iron oxide material. The mass fraction of carbon in the obtained lithium-rich lithium iron oxide is 2.4%, and the mass fraction of aluminum is 0.82%. Figure 1 As shown in FIG. 1 , the particle size of the lithium iron oxide material rich in carbon-lithium aluminate double-layer coating is in the micron level. The obtained lithium iron oxide material rich in carbon-lithium aluminate double-layer coating was exposed to air with a dew point of -20°C for 1 hour, and then an XRD test was performed. Figure 2 As shown, from Figure 2 It can be seen that after being placed in the air for 1 hour, the lithium iron oxide rich in carbon-lithium aluminate double layer did not show obvious impurity peaks and had good air tolerance. Example

[0024] Take 50g of lithium-rich lithium ferrite material, add 2g of aluminum nitrate and 0.15g of lithium oxide, mix well, and calcine at 700°C for 10h; after cooling, take out and grind, add 5g of polyvinyl pyrrolidone, mix well, and calcine at 450°C for 5h; after cooling, take out and crush, and the target product is a lithium-rich lithium ferrite material coated with a double layer of carbon-lithium aluminate. Example

[0025] Take 300g, add 4.5g of aluminum oxide and 3.3g of lithium carbonate, mix well, and calcine at 800℃ for 10h; after cooling, take out and grind, add 30g of polyethylene, mix well, and calcine at 600℃ for 4h; after cooling, take out and crush, and the target product is a carbon-lithium aluminate double-layer coated lithium iron-rich lithium material. Example

[0026] The carbon-lithium aluminate double-layer coated lithium iron-rich lithium material prepared in Example 1 is used as the positive electrode material, and the obtained carbon-lithium aluminate double-layer coated lithium iron-rich lithium positive electrode material, conductive carbon black and PVDF are mixed in N-methylpyrrolidone in a ratio of 80:10:10, ground into a paste, and coated on an aluminum foil; vacuum dried at 120°C for 12h, and cut into electrode sheets with a diameter of 12mm; the weighed electrode sheets are made into positive electrodes, metallic lithium is used as the negative electrode, a polyethylene microporous membrane is used as the diaphragm, and 1M LiClO4 (DME+PC) is used as the electrolyte, and a lithium battery is assembled in a glove box filled with argon. Example

[0027] The carbon-lithium aluminate double-layer coated lithium iron-rich lithium material prepared in Example 2 was used as the positive electrode material, and the remaining options were the same as in Example 4, and a lithium battery was assembled in a glove box filled with argon.

[0028] Comparative Example 1 Take 50g of lithium iron oxide-rich material, add 5g of glucose, mix well, and calcine at 450℃ for 5h; after cooling, take out and crush, the target product is the carbon-coated lithium iron oxide-rich material; expose the obtained lithium iron oxide-rich material to air with a dew point of -20℃ for 1h, and then perform XRD test. Figure 2 As shown, from Figure 2 It can be seen that there are impurity peaks at 2θ=30.5 and 31.7, indicating that the material decomposed after being placed in the air for 1 hour; the obtained lithium iron oxide-rich material was used as the positive electrode material, and the rest of the options were the same as in Example 4, and a lithium battery was assembled in a glove box filled with argon.

[0029] The electrochemical performance of the lithium batteries of Examples 4 and 5 was tested. The results are as follows: Figure 3 shown.

[0030] For the lithium battery of Example 4, at a rate of 0.066C, the specific charge capacity below 4.25V reaches 710mAh / g; for the lithium battery of Example 5, at a rate of 0.066C, the specific charge capacity below 4.25V reaches 690mAh / g. The electrochemical performance test results of Examples 4 and 5 show that the carbon-lithium aluminate double-layer coated lithium-rich ferrite material prepared by the method of the present invention has good lithium replenishment performance.

[0031] The electrochemical performance test of the lithium battery of Comparative Example 1 was carried out, and the results are as follows: Figure 4 As shown, at a rate of 0.066C, the charging specific capacity below 4.25V reaches 636mAh / g, indicating that the use of carbon-coated lithium-rich ferrite material alone fails to fully exert the lithium replenishment performance of lithium-rich ferrite.

[0032] In summary, compared with the lithium ferrite-rich material using only carbon coating, the lithium ferrite-rich material coated with carbon-lithium aluminate double layer prepared by the method of the present invention has better air tolerance and is not easy to decompose in the air. The lithium ferrite-rich material coated with carbon-lithium aluminate double layer of the present invention and the preparation method thereof, the lithium ferrite-rich material is uniformly mixed with the aluminum source and the lithium source, and reacts with the aluminum source and the lithium source and the surplus lithium in the lithium ferrite-rich material at high temperature to form a lithium aluminate coating layer on the surface of the lithium ferrite-rich material, and then forms a carbon-lithium aluminate double coating layer by a carbon coating method. Compared with the common carbon coating method, the lithium aluminate coating layer of the lithium-rich lithium ferrite obtained by the present invention is formed by a chemical reaction with the lithium-rich lithium ferrite at high temperature, and is tightly bonded to the surface of the lithium-rich lithium ferrite and is not easy to fall off. The carbon layer is coated on the surface of the lithium aluminate coating layer to increase the conductivity of the material, which can better resist moisture and carbon dioxide in the air, reduce the decomposition rate of the lithium-rich lithium ferrite, and fully release lithium ions through good conductivity during the lithium replenishment process, thereby achieving a better lithium replenishment effect.

[0033] The carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate and the preparation method thereof of the present invention form a lithium aluminate coating layer on the surface of the lithium-rich lithium ferrate particles after high-temperature calcination, and then the lithium aluminate-coated lithium-rich lithium ferrate is evenly mixed with a carbon-containing compound, and a carbon-lithium aluminate double coating layer is formed after high-temperature calcination. The obtained carbon-lithium aluminate double-layer coated lithium-rich lithium ferrate can better resist moisture and carbon dioxide in the air, and can fully release lithium ions during the first charging process of the lithium ion battery, thereby increasing the charging capacity.

[0034] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not limited to the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A carbon-aluminum double-layer coated lithium iron-rich lithium, characterized in that: An aluminum source is used to react and coat a layer of lithium aluminate on the surface of the lithium-rich lithium ferrite, and then a carbon source is used for coating to form a carbon-lithium aluminate double coating layer to coat the lithium-rich lithium ferrite.

2. The carbon-aluminum oxide double-layer coated lithium iron oxide rich material according to claim 1, characterized in that: The mass fraction of aluminum element is 0.2~5%, and the mass fraction of carbon element is 0.2~10%.

3. A method for preparing carbon-lithium aluminate double-layer coated lithium-rich lithium iron oxide as claimed in any one of claims 1 to 2, characterized in that: The steps include: 1) Add a certain molar ratio of lithium source and aluminum source to lithium-rich lithium ferrite powder and mix them evenly; 2) heating and calcining the mixture obtained in step 1) under an inert atmosphere, and crushing it after cooling to obtain a lithium aluminate-coated lithium ferrite-rich lithium material; 3) The lithium aluminate-coated lithium ferrite-rich material obtained in step 2) is mixed with a carbon-containing compound, heated and calcined under the protection of an inert atmosphere, and crushed after cooling to obtain a carbon-lithium aluminate double-layer-coated lithium ferrite-rich lithium material.

4. The preparation method according to claim 3, characterized in that: The lithium source is at least one of lithium hydroxide, lithium carbonate, lithium oxide, and lithium peroxide; the aluminum source is at least one of aluminum oxide, aluminum hydroxide, and aluminum nitrate; and the molar ratio of lithium element to aluminum element is 0-1.

5.

5. The method for preparing the lithium supplement according to claim 3, characterized in that: The coating temperature of lithium aluminate coated lithium-rich lithium ferrite is 600~900℃, and the coating time is 2~16h.

6. The method for preparing a lithium supplement according to claim 3, characterized in that: The coating temperature of the carbon-lithium aluminate double-layer coated lithium-rich lithium ferrite is 400~700℃, and the coating time is 1~8h.

7. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron oxide rich carbon-aluminum double-layer coated lithium iron oxide as described in any one of claims 1-2 or the lithium iron oxide rich carbon-aluminum double-layer coated lithium iron oxide obtained by the preparation method as described in any one of claims 3-6.

Citation Information

Cited By

  • Lithium-iron-silicon-niobium-oxygen composite positive electrode material and preparation method and application thereof

    CN122501870A

  • Lithium iron silicon niobium oxygen composite positive electrode material, preparation method and application thereof

    CN122501870B